2014
DOI: 10.1088/0264-9381/31/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

Naked singularity explosion in higher-dimensional dust collapse

Abstract: Abstract.In the context of the large extra dimensions or TeV-scale gravity, it has been argued that an effective naked singularity, called the visible border of spacetime, would be generated by high-energy particle collisions. Motivated by this interesting possibility, we investigate a particle creation by a naked singularity in general dimensions, adopting a spherically symmetric self-similar dust collapse as the simple model of a naked singularity formation. The power and energy of the particle emission beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…where ρ i = ρðt i Þ and a i = aðt i Þ are the initial values of energy density and scale factor, respectively, and t = t i is the initial time at which the collapse begins. Equations (12) and (13) can then be rewritten as (we set the units so that…”
Section: Solutions To the Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ρ i = ρðt i Þ and a i = aðt i Þ are the initial values of energy density and scale factor, respectively, and t = t i is the initial time at which the collapse begins. Equations (12) and (13) can then be rewritten as (we set the units so that…”
Section: Solutions To the Field Equationsmentioning
confidence: 99%
“…However, during the past decades, many examples of naked singularity formation as possible counterexamples to the cosmic censorship conjecture have been reported in the literature, among which we can quote gravitational collapse of dust, perfect fluids, and radiation shells [8,9]. Such a study has been extended to gravitational collapse in the presence of a cosmological constant term [10], higher dimensional collapse models [11][12][13][14], higher-order gravity theories [15], scalar field collapse [16][17][18][19][20], and self-similar collapse [21][22][23] (see also [2] for a recent review). Also, in the context of modified gravity theories, it is shown that naked singularities could form depending on different aspects of the theory (see, e.g., [24][25][26][27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, causal curves terminating in the past at the singularity have the chance to reach the faraway observers thus exposing super-dense regions of extreme gravity to the external universe. [10,11] In this context, formation of naked singularities as collapse outcome has been studied within many different scenarios such as gravitational collapse of a dust cloud, [12] scalar fields' collapse, [13][14][15][16][17][18][19] gravitational collapse in higher dimensions [20][21][22][23][24][25][26] etc. (for a review see refs.…”
Section: Introductionmentioning
confidence: 99%